Distribusi dan tingkah laku Hiu Paus (Rhincodon typus) di perairan Kwatisore Taman Nasional Teluk Cenderawasih Provinsi Papua Tengah - Suruan, Sampari Saneraro; Manangkalangi, Emmanuel; Simatauw, Fanny F. C; Tebaiy, Selvi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Research on the whale shark (Rhincodon typus) is carried out in the Kwatisore waters, part of the Cenderawasih Bay National Park (CTNP), Papua, Indonesia. Field observations were conducted for 4 months, from September to December 2016. The objective of the study was to look at the distribution and behavior of whale sharks based on weather conditions, time and place of appearance. The collecting of whale shark data was done by direct observation method which was divided into 2 observation time that is direct observation by researchers between 06.00-17.59 WIT and indirect observation by lift-net fisherman between 18.00-05.59 WIT. The distribution of whale sharks will be analyzed using Geographic Information System (GIS) through digitization process and overlay based on coordinate point. The results of observation and data analysis showed that the frequency of whale shark emergence at 06.00-11.59 WIT is much higher than at 00.00-05.59 WIT that is 148: 18 times. The low frequency of occurrence of these fish at night because in every observation at night, it is difficult to find an individual whale shark that appears. Whale sharks are more visible when the weather is sunny, compared to overcast or rainy days. The results of behavioral observations show that 64% of whale sharks appear to be eating. The rest is playing and just passing by. This is because whale sharks are heavily dependent on the main food of plankton that often lies just below the surface of the waters and or on the surface of the waters.